(untitled) (Sebha University Conference Proceedings, 2024)
The occurrence of natural radioactivity in the environment is attributable to the primordial and cosmogonist nuclides in the earth’s crust where the exposure associated with this natural radioactivity relies principally on the geological and geographical environments. In this paper, Natural-radionuclide levels 238U, 226Ra, 232Th and 40K were determined and investigated in seashore sediment samples collected from an area on the Eastern Coast of Libya (Al Jabal Al Akhdar region). The goal of this research is to evaluate radionuclide’s concentrations and their distribution in this region. The measurement of natural radioactivity concentrations in the sediment samples was performed employing gamma-ray spectrometry techniques using a pure germanium detector (HPGe). The extracted values of the activities for238U, 226Ra,232Th, and40K were in the range of values obtained in similar studies in other countries and are within the average worldwide values. The calculated average values of radioactivity concentrations for 238U, 226Ra, 232Th and 40K were 7.75, 8.53, 3.16 and 13.26 Bq/kg, respectively. The descriptive statistical features of radioactive levels in sediment samples are also presented. Due to the limited similar studies in the study area, the obtained results could assist in setting up a reference line of radiometric records for radioprotection purposes and environmental monitoring schemes in the study area and in Libya in general.